2013
DOI: 10.1007/s10787-013-0186-4
|View full text |Cite
|
Sign up to set email alerts
|

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis

Abstract: This study investigated the mechanism of the cytotoxic effect of emodin, an active anthraquinone, on human lung adenocarcinoma A549 cells. In vitro growth inhibition and suppression on colony forming were used to evaluate the effects of emodin on A549 cells. Emodin's ability in changing the expressions of apoptosis-related genes was studied by real-time RT-PCR. Emodin could significantly inhibit the growth of A549 cells with IC50 = 16.85 μg/ml (~60 μM). It also concentration dependently inhibited the colony-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Emodin is derived from rhubarb and numerous other plants, and has demonstrated antibacterial, antiviral, anti-inflammatory and anticancer effects (15). However, previous studies have revealed that emodin inhibits cell growth in several types of cancer cells by regulating genes related to apoptosis, oncogenesis, proliferation and cancer cell invasion and metastasis (10,16,17). Notably, emodin inhibited epithelial-mesenchymal transition, suggesting that emodin may have anticancer effects (18).…”
Section: Discussionmentioning
confidence: 99%
“…Emodin is derived from rhubarb and numerous other plants, and has demonstrated antibacterial, antiviral, anti-inflammatory and anticancer effects (15). However, previous studies have revealed that emodin inhibits cell growth in several types of cancer cells by regulating genes related to apoptosis, oncogenesis, proliferation and cancer cell invasion and metastasis (10,16,17). Notably, emodin inhibited epithelial-mesenchymal transition, suggesting that emodin may have anticancer effects (18).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, emodin (IC 50 = 3.70 µ m ) was shown to modulate the expression of apoptosis‐related genes to induce growth inhibition and apoptosis in A549 cells. Treatment with emodin helped to enhance apoptosis in A549 cells through up‐regulation of the gene expression of Fas ligand (FASL) and disabled damage repair in A549 cells through down‐regulation of the gene expression of C‐MYC (Li et al ., ). Emodin could induce growth inhibition and apoptosis in MCF‐7 cells through the modulation of the expression of apoptosis‐related genes.…”
Section: Pharmacologymentioning
confidence: 97%
“…In these experiments, treatment with essential oil of C. sylvestris at 4.0 µg/ml reduced the colony-forming ability of A549 cells to 6% of the value obtained with the control. This effect could be due to interference of essential oil in the membrane integrity, DNA fragmentation or mitochondrial depolarization (Li et al, 2014;Ruan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%